The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3758/bf03196369
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory imagery: A review

Abstract: Olfaction's unique cognitive architecture, the apparently inconsistent evidence favoring imagery, and its difficulty of evocation have led some to conclude that there is no capacity for olfactory imagery. Using three streams of evidence, we examine the validity of this claim. First, self-reports of olfactory imagery can resemble those obtained for actual perception. Second, imagining an odor can produce effects similar to actual perception. Third, olfactory perception and memory-based images can interact. A mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 178 publications
(227 reference statements)
6
86
0
1
Order By: Relevance
“…A classic response in this regard is to claim that anatomically, olfactory and semantic memory are relatively remote and are sparsely interconnected (see Stevenson & Case, 2005b). However, we know of no data that strongly support this suggestion, and it has been criticized on just such grounds (e.g., Lorig, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classic response in this regard is to claim that anatomically, olfactory and semantic memory are relatively remote and are sparsely interconnected (see Stevenson & Case, 2005b). However, we know of no data that strongly support this suggestion, and it has been criticized on just such grounds (e.g., Lorig, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot be sure that participants utilize phenomenal imagery to complete such tasks, studies such as these offer qualified support for the existence of an odor imagery capacity. Second, although there are many reports of failures to obtain imagery effects (see Stevenson & Case, 2005b), it is a characteristic of these null results that participants were never taught to associate the odorant with its verbal (or visual) referent. Third, many participants spontaneously sniff when asked to form an odor image.…”
mentioning
confidence: 98%
“…Evidence for olfactory imagery would be consistent with the notion of an olfactory slave system in working memory. In a review of the olfactory imagery literature, Stevenson and Case (2005) concluded that people can imagine odours, but that they often find it hard to do so without practice. Djordjevic, Zatorre, Petrides, and Jones-Gotman (2004) demonstrated perceptual effects of olfactory imagery similar to those of visual imagery on visual perception (Segal & Fusella, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…However, one major problem of the olfactory sense being a near sense and often relying on our sense of vision to find its source is that potentially what we see may influence our perception of the odours we perceive. A number of research studies [6,69,76] have shown that this is indeed mostly the case.…”
Section: Olfactory Data Issues In Computingmentioning
confidence: 93%